Critical Discourse Analysis of How Online News Construct Public Opinion During Campaigns - Sinaga, Tantiara Fiesta; Beru Sembiring, Inggrid Gavrila; Putri, Dian Marisha (Journal of English Language and Education, 2025)
In the digital age, online news platforms significantly shape public opinion, especially during political campaigns. However, little attention has been given to how linguistic and ideological strategies in online journalism construct meanings that influence democratic perception. This study investigates how Kompas, CNN Indonesia, and BBC News construct public opinion during the 2024 Indonesian presidential campaign using Norman Fairclough’s three-dimensional model of Critical Discourse Analysis (CDA). Through qualitative analysis, the study examines textual, discursive, and sociocultural dimensions to reveal how media discourse emphasizes campaign scale, continuity, and spectacle over substantive policy debates. Findings indicate that online news constructs campaigns as performances of mobilization and legitimacy, reinforcing dominant narratives of stability and progress. The study concludes that online news does not merely report politics but actively shapes democratic understanding through linguistic framing and ideological representation.